The opposing forces of the intestinal Microbiome and the emerging pathobiome - Defazio, Jennifer (Surg Clin North Am, 2014)
OBJECTIVE: The purpose of this article is to summarize emerging concepts on the role of the intestinal microbiome in surgical patients. BACKGROUND: Revolutionary research over the past decade has shown that human beings live in close and constant contact with boundless communities of microbes. This new reality has wide-ranging implications for the care of surgical patients. METHODS AND RESULTS: Recent innovations in the study of the human microbiome are reviewed. To demonstrate the applicability of these studies to surgical disease, we discuss in detail what is known about the role of microbes in the pathogenesis of perioperative complications including anastomotic leak, sepsis, and surgical site infections. CONCLUSIONS: Enhanced awareness of the human microbiome will empower clinicians to adopt novel practices in the prevention and treatment of a wide variety of surgical conditions.